Análise de terrenos na porção setentrional da Província Borborema, NE do Brasil: integração de dados geológicos e gravimétricos - Campelo, Romário Carvalho (1999)
It is presently assumed that the Borborema Province resulted from a complex collisional process associated with the convergent movement of plates, possibly involving amalgamation and accretion of microplates. This process was consolidated at the end of the Brasiliano event. It is investigated the possible limits for the tectonostratigraphic terranes in the northern portion of the province based on an integrated study of geological and gravity data. The study area comprises the portion of the Borborema Province located north of the Patos Lineament, limited by longitudes 33º00 W and 43º29 44"W and latitudes 1º36 S and 8º00 S. A revision of the regional geology allowed to identify areas presenting contrasting geological attributes, possibly representing different terranes whose limits are always shear zones of Brasiliano-age. The Sobral-Pedro II shear zone is the only one undoubtedly presenting geological attributes of sutures zones. The other shear zones are very likely associated with a geodinymic context of accretion, involving oblique collisions (docking), transcurrent and/or transforming sutures, and deep intracrustal shear zones. The gravity data contributed as a tool to identify strong lateral contrasts of density inside the upper crust possibly associated with crustal blocks tectonically juxtaposed. The dominant long wavelength anomaly in the Bouguer anomaly map is an expressive gradient, grossly parallel to the continental margin, caused by density variation across the crust-mantle interface in the transition from the continental crust to the oceanic crust originated by the separation between South America and Africa. Medium to small wavelength anomalies are due to intracrustal heterogeneities such as different Precambrian crustal blocks, Brasiliano-age granites and Mesozoic sedimentary basins. A regional-residual separation of the Bouguer anomaly map was performed in order to enhance in the residual map the effect due to intracrustal heterogeneities. The methodology used for this separation was a robust polinomial fitting. The inversion of residual gravity field resulted in a density contrast map (Δρ), in an equivalent layer that provided more accurated anomalies contours and consolidated the model which the sources of residual anomalies are located in the upper part of the present crust. Based on the coincidence of gravity lineaments in the residual map and Brasiliano shear zones, and using additional geological information, the following shear zones are proposed as limits between terranes: Patos shear zone, Sobral-Pedro II shear zone, Picuí-João Câmara shear zone, Remígio-Pocinhos shear zone, Senador Pompeu shear zone, Tauá shear zone, and Portalegre shear zone. Based on the geological/geophysical information it is attributed a higher level of confidence to the first three proposed limits(Patos, Sobral Pedro II, and Picuí-João Câmara shear zones). From west to east, these shear zones individualize the following terranes: Northwest of Ceará terrane, Central Ceará terrane, Tauá terrane, Orós-Jaguaribe terrane, Seridó terrane, and São José de Campestre terrane. In our study, the Rio Piranhas and Patos terranes are questioned because their previously proposed limits do not present good geological and gravimetric evidences. On the other hand, the previously proposed Cearense terrane is now subdivided into Central Ceará and Tauá terranes. Two residual gravity profiles located in the Seridó belt were interpreted using 2 ½ D direct gravity modeling. The main result of the modeling process is that all anomalies, with the exception of one, can be explained by outcroppring bodies, therefore restricted to the upper part of the present crust